Effect of tree evapotranspiration and hydrological processes on urban microclimate in a tropical city: A WRF/SLUCM study - Li, Xian-Xiang; Liu, Xuan (Urban climate, 2021)
Evapotranspiration effect of urban vegetation has been recognized to mitigate the urban thermal stress such as urban heat island (UHI) effect. Continuing from the previous offline study on the effect of tree evapotranspiration, this study employs the Weather Research and Forecasting (WRF) model coupled with Single-Layer Urban Canopy Model (SLUCM) to investigate the effect of tree evapotranspiration on the urban microclimate in the tropical city Singapore. The improved WRF/SLUCM model incorporating tree evapotranspiration and enhanced hydrological processes is evaluated against observed surface energy balance and near-surface variables (air temperature and humidity). The simulation results demonstrate that both tree evapotranspiration and hydrological processes increase the latent heat flux and reduce sensible heat flux by different magnitudes in different urban land use types, with the impact by hydrological processes larger. The impact on the fluxes is mostly during daytime and relatively small during nighttime. However, the change in surface energy balance by tree evapotranspiration only causes limited changes in 2-m air temperature and humidity, showing little effect on the thermal environment. The change induced by hydrological processes, i.e., treating a portion of anthropogenic heat as latent heat flux, can impact the temperature and humidity more, especially in the commercial/industrial areas. Comparison with other similar studies in literature suggests that the Singapore's hot, humid climate and low tree coverage in urban areas may contribute to this finding. This study also highlights the necessity of considering the latent component of anthropogenic heat. •Improved WRF/SLUCM is used including hydrological processes and tree evapotranspiration in Singapore.•Both increase the latent heat flux and reduce sensible heat flux by different magnitudes.•Tree evapotranspiration induces little change in 2-m temperature and humidity.•Hydrological processes impact 2-m temperature and humidity more than tree evapotranspiration.